Evaluation of Properties of Dikiri Pulp in the Formulation of Jam - Gunathilake, K. D. P. P.; Samarasinghe, D. N. H. (International Coconut Community Journal, 2015)
The peculiar farm of coconut,” Dikiri” was studied for its kernel composition including pectin content with the objective of developing a jam out of Dikiri kernel. Three levels of Dikiri pulp, 20%, 30% and 40%, were evaluated to prepare Dikiri based jam. Two types of jam were prepared; Jam made with Dikiri only as the fruit pulp and the jam with Dikiri pulp together with 10% pineapple. They were tested for sensory attributes and were compared with pineapple jam prepared with added commercial high methoxyl pectin. The best jam was selected for shelf life study at room temperature. Results showed that Dikiri kernel differs from ordinary coconut for all the variables tested in proximate composition analysis. Dikiri kernel contained 16.6% of high methoxyl pectin on a dry weight basis. The jam with 30% Dikiri pulp was selected as the best total pulp ratio and the incorporation of 10% pineapple pulp into Dikiri gives better sensory properties compared with Dikiri only jam. In conclusion, there is a possibility of formulation of jam without adding external pectin with considerable sensory acceptability and good keeping quality.